2018
DOI: 10.1016/j.ultsonch.2017.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effect in sonochemical synthesis of metal-alloy nanoparticles for use as electrocatalysts

Abstract: Nanomaterials are now widely used in the fabrication of electrodes and electrocatalysts. Herein, we report a sonochemical study of the synthesis of molybdenum and palladium alloy nanomaterials supported on functionalized carbon material in various solvents: hexadecane, ethanol, ethylene glycol, polyethylene glycol (PEG 400) and Ionic liquids (ILs). The objective was to identify simple and more environmentally friendly design and fabrication methods for nanomaterial synthesis that are suitable as electrocatalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…This may be because an increase in the ultrasonic time enabled the OPO to be sufficiently dissolved within a specific range. When the time exceeded 40 min, the extraction rate of OPO decreased slightly with time, which was caused by the high temperature of the solvent [29]. Therefore, when the amount of evaporation of OPO increased, its yield would drop.…”
Section: Resultsmentioning
confidence: 99%
“…This may be because an increase in the ultrasonic time enabled the OPO to be sufficiently dissolved within a specific range. When the time exceeded 40 min, the extraction rate of OPO decreased slightly with time, which was caused by the high temperature of the solvent [29]. Therefore, when the amount of evaporation of OPO increased, its yield would drop.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, at longer pulse sonication times, the number of active bubbles decreases due to the degassing [30]. Therefore, in order to maximize the cavitation efficiency, the optimum pulse sonication must be identified [62]. In our case, the minimum band-gap energy was achieved with an on-off pulse of 1-1 s.…”
Section: The Effect Of Ultrasound Pulsesmentioning
confidence: 85%
“…In addition, high power/amplitude causes undesired effects, such as the degradation of molecular structures. High power disrupts the bubble dynamic as it grows, and this leads to poor cavitation and growth of the material [62]. Additionally, at high power/amplitude, the removal efficiency of the deposit increases and there is less chance of crystallization [63].…”
Section: The Effect Of Ultrasound Powermentioning
confidence: 99%
“…Saien and Hashemi [84] used 1-hexadecyl-3-methyl imidazolium chloride IL as a surfactant to study its interaction with Fe 3 O 4 nanoparticles in a biphasic oil/water system. In a study by Okoli et al [85] it was found that the sole use of ILs without additional co-surfactants is capable of producing good quality (monodispersity with narrow size distribution) metal alloy nanoparticles which display enhanced catalytic activities. A pre-concentration technique based on the use of graphene oxide (GO) functionalized with an IL was established for the determination of Hg traces in water [86].…”
Section: Practical Examples Of Imidazolium-based Ils Used In the Syntmentioning
confidence: 99%